Living Hadis Berjama’ah Shalat Empat Puluh Hari Pada Masyarakat Desa Salam Kecamatan Gebang Kabupaten Purworejo - Musolin, Muhlil; Mukhtar, Naqiyah (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2023)
The people of Salam Village, Gebang District, Purworejo Regency carry out the congregational prayer tradition for forty consecutive days. This study takes the formulation of the problem, namely how to implement congregational prayers for forty days in the Salam Village community. The purpose of this research is to find out the implementation of congregational prayers for forty consecutive days in the Salam Village community. The approach used in this research is a descriptive qualitative approach using analysis, process and meaning. This type of research is field research. The time of this research was carried out in March-June 2022 in Salam Village, Gebang District, Purworejo Regency. The object of research is the behavior of congregational prayer for forty consecutive days of Salam village residents, Gebang District, Purworejo Regency. Data collection techniques using observation, interviews and documentation with data analysis through the steps of data documentation, data reduction, displaying data and drawing conclusions. The results of the study indicate that the congregational prayer for forty consecutive days in the Salam Village community departs from the Prophet's orders. in the hadith narrated by Tirmidhi. The Salam Village community in understanding the hadith recommending congregational prayers for forty consecutive days using the textual method, where they focus on two virtues that will be obtained for anyone who does it, namely being free from hellfire and free from hypocrisy. The public's reception of congregational prayers for forty consecutive days can be said to be very good, where the enthusiasm of the Salam Village community towards praying congregational prayers for forty consecutive days is quite good, it can be seen that participants pray in congregation for forty consecutive days this has a relatively large number. The benefits of carrying out congregational prayers for forty days in a row are getting used to praying in congregation, being more disciplined in time and not a few mentioning that when praying in congregation for forty days in a row they can meet with relatives.